2021
DOI: 10.1002/ejoc.202001469
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Insights into Asymmetric Rh‐Catalyzed Hydrocarboxylation with CO2

Abstract: The asymmetric Rh-catalyzed hydrocarboxylation of α,β-unsaturated carbonyl compounds was originally developed by Mikami and co-workers but gives only moderate enantiomeric excesses. In order to understand the factors controlling the enantioselectivity and to propose novel ligands for this reaction, we have used computational and experimental methods to study the Rh-catalyzed hydrocarboxylation with different bidentate ligands. The analysis of the CÀ CO 2 bond formation transition states with DFT methods shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Afterward, the Mikami group 10 reported the catalytic asymmetric hydrocarboxylation of the prochiral α,β-unsaturated esters with CO 2 by using the cationic ( S )-SEGPHOS-Rh complex as the catalyst and AgSbF 6 as the cocatalyst, which led to the corresponding carboxylation product with moderate enantioselectivity (66% ee value). Of note, the Hopmann group 11 carried out the computational and experimental approaches to understand the factors that control the enantioselectivity in such reaction systems. Their DFT calculations showed that CO 2 insertion into the substrate preferably undergoes an outer -sphere C–CO 2 bond formation transition state, where the Rh centre is η 6 chelated with the phenyl ring of the substrate, and is far away from the nucleophile CO 2 simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, the Mikami group 10 reported the catalytic asymmetric hydrocarboxylation of the prochiral α,β-unsaturated esters with CO 2 by using the cationic ( S )-SEGPHOS-Rh complex as the catalyst and AgSbF 6 as the cocatalyst, which led to the corresponding carboxylation product with moderate enantioselectivity (66% ee value). Of note, the Hopmann group 11 carried out the computational and experimental approaches to understand the factors that control the enantioselectivity in such reaction systems. Their DFT calculations showed that CO 2 insertion into the substrate preferably undergoes an outer -sphere C–CO 2 bond formation transition state, where the Rh centre is η 6 chelated with the phenyl ring of the substrate, and is far away from the nucleophile CO 2 simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…For insertion of CO 2 into metal–R bonds (R = hydride or alkyl/aryl), generally two mechanisms can be considered (Scheme A): i ) An inner sphere path , involving an interaction between CO 2 and the metal at the transition state for H–CO 2 bond formation (TS inn ). , Note that a precoordination of CO 2 is not required ,,, Subsequently, the resulting η 1 -σ-intermediate rearranges (TS2) , to allow for formation of a κ 1 -O-(or κ 2 -O,O-)­carboxylate species. It is important to note that although TS inn and TS2 both are cyclic, they are entirely different transition states, whose optimized geometries will show distinct features.…”
Section: Introductionmentioning
confidence: 99%